Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(dkxd\Leftrightarrow\hept{\begin{cases}x\ge0\\\sqrt{x}-2\ne0\end{cases}\Rightarrow\hept{\begin{cases}x\ge0\\x\ne4\end{cases}}}\)
\(A=\left(\frac{\sqrt{x}}{x-4}-\frac{2}{\sqrt{x}-2}+\frac{1}{\sqrt{x}+2}\right):\frac{1}{\sqrt{x}+2}.\)
\(=\left(\frac{\sqrt{x}}{x-4}-\frac{2\left(\sqrt{x}+2\right)}{x-4}+\frac{\sqrt{x}-2}{x-4}\right):\frac{1}{\sqrt{x}+2}\)
\(=\frac{\sqrt{x}-2\sqrt{x}-4+\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}.\frac{\sqrt{x}+2}{1}\)
\(=\frac{-6\left(\sqrt{x}+2\right)}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}=-\frac{6}{\sqrt{x}-2}\)
\(A=\)\(\left(\frac{\sqrt{x}}{x-4}+\frac{2}{2-\sqrt{x}}+\frac{1}{\sqrt{x}+2}\right)\)\(:\frac{1}{\sqrt{x}+2}\)
a,ĐKXĐ:\(\hept{\begin{cases}x\ge0\\2-\sqrt{x}\\x-4\ne0\end{cases}\ne0}\)\(\Rightarrow\)\(\hept{\begin{cases}x\ge0\\x\ne4\end{cases}}\)
\(A=\)\(\left(\frac{\sqrt{x}}{x-4}+\frac{2}{2-\sqrt{x}}+\frac{1}{\sqrt{x}+2}\right)\)\(:\frac{1}{\sqrt{x}+2}\)
\(A=\)\(\left(\frac{\sqrt{x}}{x-4}-\frac{2}{\sqrt{x}-2}+\frac{1}{\sqrt{x}+2}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\left(\frac{\sqrt{x}-2\left(\sqrt{x}+2\right)+\sqrt{x}-2}{x-4}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\left(\frac{\sqrt{x}-2\sqrt{x}-4+\sqrt{x}-2}{x-4}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\left(\frac{-6}{x-4}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\frac{-6}{\sqrt{x}-2}\)
b,\(x=9-4\sqrt{5}\)\(\Rightarrow\)\(A=\)\(\frac{-6}{\sqrt{9-4\sqrt{5}}-2}\)\(=\frac{-6}{\sqrt{5-2.2\sqrt{5}+4}-2}\)
\(A=\)\(\frac{-6}{\sqrt{\left(\sqrt{5}-2\right)^2}-2}\)\(=\frac{-6}{\sqrt{5}-2-2}\)\(=\frac{-6}{\sqrt{5}-4}\)
c,\(A>-1\)\(\Rightarrow\)\(\frac{-6}{\sqrt{x}-2}\)\(>-1\)\(\Rightarrow\)\(\frac{-6}{\sqrt{x}-2}+1>0\)
\(\Leftrightarrow\)\(\frac{-6+\sqrt{x}-2}{\sqrt{x}-2}>0\)
\(\Leftrightarrow\)\(\frac{\sqrt{x}-8}{\sqrt{x}-2}>0\)
a. A=Đề=\(\frac{\sqrt{x}-\sqrt{x-1}-\sqrt{x}-\sqrt{x-1}}{\left(\sqrt{x}+\sqrt{x-1}\right)\left(\sqrt{x}-\sqrt{x-1}\right)}+\frac{x\left(1-\sqrt{x}\right)}{1-\sqrt{x}}\)\(\left(ĐKXĐ:x>1\right)\)
\(=\frac{-2\sqrt{x-1}}{x-x+1}+x\)\(=x-2\sqrt{x-1}\)
b. A>0 \(\Leftrightarrow x-2\sqrt{x-1}>0\)
\(\Leftrightarrow x>2\sqrt{x-1}\)\(\Rightarrow x^2>4\left(x-1\right)\)\(\Leftrightarrow x^2>4x-4\)
\(\Leftrightarrow x^2-4x+4>0\)\(\Leftrightarrow\left(x-2\right)^2>0\)\(\Rightarrow x-2>0\)
\(\Leftrightarrow x>2\)
a) A= \(\frac{1}{\sqrt{x}+\sqrt{ }x-1}\) - \(\frac{1}{\sqrt{x}-\sqrt{x-1}}-\frac{x\sqrt{x}-x}{1-\sqrt{x}}\) với x>1\(\frac{\sqrt{x}-\sqrt{x-1}}{x-\left(x-1\right)}-\frac{\sqrt{x}+\sqrt{x-1}}{x-\left(x-1\right)}+\frac{x\left(\sqrt{x}-1\right)}{\sqrt{x}-1}\) \(=\frac{\sqrt{x}-\sqrt{x-1}-\sqrt{x}-\sqrt{x-1}}{1}+x\) \(=-2\sqrt{x-1}+x\) b) với x>1 ta có A>0 hay \(-2\sqrt{x-1}\)\(+x\)\(>0\)\(\Rightarrow x>2\sqrt{x-1}\)\(\Leftrightarrow\)\(x^2>4\left(x-1\right)\Leftrightarrow x^2-4x+4>0\)\(\left(x-2\right)^2>0\)(--> \(x\ne\pm2\) )
1111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111
ĐK : tự ghi nha
\(A=\frac{x\sqrt{x}+1}{x-1}-\frac{x-1}{\sqrt{x}+1}\)
\(A=\frac{\sqrt{x}^3+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}-\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}{\sqrt{x}+1}\)
\(A=\frac{\left(\sqrt{x}+1\right)\left(x-\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}-\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}{\sqrt{x}+1}\)
\(A=\frac{x-\sqrt{x}+1}{\sqrt{x}-1}-\sqrt{x}-1\)
\(A=\frac{x-\sqrt{x}+1}{\sqrt{x}-1}-\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}-1}\)
\(A=\frac{x-\sqrt{x}+1}{\sqrt{x}-1}-\frac{x-2\sqrt{x}+1}{\sqrt{x}-1}\)
\(A=\frac{x-\sqrt{x}+1-\left(x-2\sqrt{x}+1\right)}{\sqrt{x}-1}\)
\(A=\frac{x-\sqrt{x}+1-x+2\sqrt{x}-1}{\sqrt{x}-1}\)
\(A=\frac{\sqrt{x}}{\sqrt{x}-1}\)